Two-sided matching for hesitant fuzzy numbers in smart intelligent technique transfer. (May 2020) - Yue, Qi; Zhang, Lili
Highlights: The smart intelligent technique transfer problem with hesitant fuzzy numbers (HFNs) is studied. A novel score function of HFNs is proposed. A two-sided matching model with score functions is developed. The matching scheme is obtained by solving the model. Some comparing analyses are conducted. Abstract: Hesitant fuzzy set (HFS), as an extension of fuzzy set, is deemed as a very useful mean to exhibit hesitant information in handling real-life problems. To enlarge the range of applicability, this paper combines HFS with two-sided matching (TsM). Firstly, this paper retrospects the definitions of hesitant fuzzy Numbers (HFNs) and TsMs, where a new score function of HFN is provided. After that, the TsM decision problem based on HFNs is demonstrated. To solve it, a TsM decision model on the basis of HFNs is built. Through using linear weighted method, the TsM model is transformed into a two-goal TsM model. Moreover, the two-goal TsM model with HFN can be changed to a single-goal TsM model with scores through using the introduced score function. The "soundest" alternative of TsM could be acquired through model solution. Lastly, an example in smart intelligent technique transfer is used to state the feasibility and validity of the presented method.